Estrogenic and serotonergic butenolides from the leaves of Piper hispidum Swingle (Piperaceae) - Michel, Joanna L. (2010)
Publisher copyright policies & self-archiving: Author's Pre-print: author can archive pre-print (ie pre-refereeing). Author's Post-print: author can archive post-print (ie final draft post-refereeing). Publisher's Version/PDF: author cannot archive publisher's version/PDF. Documento privado